Investigation of the Effect of Hot Fluid on Deformation in T-Shaped Pipes by FSI Method Using Different Material - Haydar Kepekçi; Erman Aslan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, the high-temperature liquid water flow through the cross-section of a T pipe and the effect of the temperature of the liquid on the pipe material has been investigated. Pipe deformation caused by fluid temperature has been analyzed by the Fluid-structure interaction method. The effect of temperature distribution inside the pipe has been considered as thermal load in the structural analysis of the pipe body. The finite volume method has been used in the study with numerical methods. While k-ε is preferred as the turbulence model, the mesh file created to be used in the analysis contains 200,000 grid cells. For all calculations, the Reynolds number has been set to 3900 and kept constant. The geometry of the T pipe, the fluid passing through the pipe and used the boundary have been constant for the numerical analysis made in the study. The pipe material has been determined as the only parameter that changed. As different pipe materials magnesium, aluminum, copper, steel, concrete, cast iron, and titanium have been used. As a result of the study, thermal strain, total deformation, and directional deformation values have been determined. As a result, it has been determined that the greatest deformation under thermal load is in magnesium pipes, and the smallest deformation is in titanium pipes. It has been observed that the total amount of deformation of the pipe made of magnesium is three times higher than that of the titanium pipe.